A Sociolinguistic Analysis of Register Usage by Members in the “Ikan Hias Kediri (Ihk) *Reborn*” Fish Trading Group In Facebook - Fekaliza Deprin Suharyanto; Salma Cindyaisya; Yuca Dewi Kurniawati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2024)
The Facebook buying and selling community "Ikan Hias Kediri (ihk) Reborn" is interesting to analyze because the group uses many words and phrases.the members of this group number around seventeen thousand members. The "Ikan Hias Kediri (ihk) Reborn" Facebook buying and selling community is one of the groups of buying and selling communities on Facebook. This community provides a place for its members to conduct buying and selling fish and accessories transactions in the Kediri area and its surroundings. There are many words and phrases used in the community such as "Slayer", "Tank", "Casut", "RTC", and others. The researcher will analyze the register used in the Facebook buying and selling community “Ikan Hias Kediri” (ihk) “Reborn” as research material.